P6_7 Doom Divers - Edkins, Troy; Loch, Callum; Nicholls, Tristram; Woodcock, Nathaniel (Physics Special Topics, 2022)
In this paper the feasibility of a catapult launching a goblin in a crude wing-suit used to guide itself to its target is discussed. The forces experienced by the goblin at launch are calculated to be roughly 336g for 0.055s, enough to severely injure them. The maximum range of such a catapult, with the wing's effect taken into account, would be 3km. It is found that the goblin would not serve any purpose beyond a dumb projectile, rendering the main purpose of the catapult obsolete.